Syria: the challenges of parenting in refugee situations of immediate displacement. Issue 2 (July 2016) - El-Khani, Aala; Ulph, Fiona; Peters, Sarah; Calam, Rachel
Abstract : The way parents care for their children during displacement plays a key role in children's emotional and behavioural outcomes. Yet, sparse literature exists regarding the parenting challenges faced by families fleeing conflict in transitional, pre-resettlement stages. This study, therefore, aimed to identify the parenting experiences of Syrian families living in refugee camps, focusing on understanding how their parenting had changed and the impact displacement had had on their parenting. Methods used included: interviews and focus groups discussions with 27 mothers living in refugee contexts, two interviews with professional aid workers, with the data analysed using thematic analysis. Data were structured in three themes; 1) environmental challenges; 2) child specific challenges; and 3) parent specific challenges. Results clearly showed that parents struggled physically and emotionally to support their children. Such challenges could be addressed by parenting interventions to reduce the trauma impact experienced by children.